TINJAUAN YURIDIS TERHADAP PERAN BADAN PENANAMAN MODAL DAN PERIZINAN TERPADU TERKAIT KAWASAN PERUNTUKAN INDUSTRI DI SENTOLO KULON PROGO - , Faradilla Melina Jannah ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to know role of Investment and Integrated Licensing Board (BPMPT) in allotment designation of industrial areas in Sentolo Kulon Progo once the obstacles related increasing investment encountered and the mitigation efforts. This study empirical jurisdiction, the research and analyzing secondary data which is followed by research and analyzing primary data. Qualitative analysis method is used to both secondary data and primary data, which is done by gathering and selecting secondary data from field studies to and connected with the theory obtained from the literature that can be obtained answers to the problems. Furthermore, the results presented descriptively. The research results indicate that Investment and Integrated Licensing Board (BPMPT) role as the licensing services implementer